Preparation and characterization of self-aggregating micelles from stearic acid-modified burdock root polysaccharide - Chenchen Zhang; Hongjuan Wang; Yan Zhang; Jiangfeng Song; Ying Li (Food Production, Processing and Nutrition, 2024)
Abstract In order to obtain amphiphilic polysaccharide self-assembly micelles, the hydrophobic modification by grafting stearic acid (SA) onto the backbone of burdock root polysaccharide (BRP) was carried out and its main physicochemical properties were characterized. The results showed that the optimal esterification conditions were as follows: reaction time of 2 h, reaction temperature of 55 ℃, system pH of 8.0 and the SA addition of 4 mmol, a maximum substitution degree (DS) of the esterification products was obtained as 0.1012. The FTIR analysis verified that the modified polysaccharide successfully introduced the ester carbonyl group. 1H NMR spectra further confirmed that the esterification reaction occurred. The SA-modified BRP micelles were roughly spherical with uniform dispersion and the particle size was in the range of 259–352 nm, which showed a negative correlation with the DS. The solubility of the esterification products also decreased. The smaller critical micelle concentration (CMC) led to easier formation of self-aggregating micelles and stronger solubilization effect. The above results indicated that SA-modified BRP as a novel carrier material possessed potential to deliver hydrophobic active substances. Graphical Abstract